Livestock marketing in eastern Kajiado, Kenya - Bekure, S.; Chabari, F.N. (Winrock International, 1986)
Reports on a study of livestock marketing conducted in eastern Kajiado, Kenya. Describes major market areas, the operation of the cattle market including the sources, characterstics and prices of the cattle trade, the efficiency of the market and the problemes encontered by the buyeres and selleres.